Revisiting the Trade-Creating Effects of Non-Tariff Barriers - Gabriel Felbermayr; Feodora Teti (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Modern regional trade agreements focus on promoting bilateral exchange mostly by lowering non-tariff barriers to trade. But do existing regional trade agreements actually deliver what they promise? This paper argues that existing results in the literature are upward biased because of measurement error in a crucial control variable: tariff rates. Using a novel data set of high-quality tariff information, the paper shows that, on average, non-tariff barriers reductions in deep regional trade agreements boost services trade but not goods trade. Estimating separate non-tariff barrier effects for each regional trade agreement reveals strong heterogeneity: only 23 percent of all regional trade agreements seem to lower non-tariff barriers. For most regional trade agreements, we fail to find any significant effect, while 9 percent appear to reduce trade, possibly because a more balanced regulation evens out comparative advantages. The trade agreements that foster trade the most include non-discriminatory trade policy changes.
Keywords: F13; F14; 330; RTAs; non-tariff barriers; trade policy; tariffs